Informal Capital Markets and Integrated Rural Development in Nigeria - Ntiedo B. Ekpo (European Scientific Journal, ESJ, 2016)
The study examined the effects of informal capital markets on people-oriented development at the grassroots level in Nigeria. It was motivated by the prevalent speculations and differences of opinion in the literature about the effects of the markets on rural development in most third world countries, including Nigeria. The study adopted the exploratory survey research design and used mean score and Mann-Whitney U test in analyzing the data. The outcome of the analysis, among others, shows first, that all the benchmarks for rural developments, such as poverty reduction, women empowerment and housing development, were significantly related to informal capital market participation. Second, the utilization of micro credits was a major factor in the profitability and growth of business in the rural areas. It is recommended that the monetary authorities and other policymakers recognize the cooperative finance efforts of this group of financial institutions, and devise appropriate means of integrating it with the formal financial sector for improved financial intermediation and wellbeing of the rural poor as well as sustainable growth of the national economies.